PERGE'DEN RAHİP APOLLONIOS'UN ZEUS SOTER'E SÜTUN ADAĞI. - KİLECİ, ŞENKAL (CEDRUS, 2019)
This article introduces an inscribed violetveined column found during the excavations in Perge in 2014. The violet-veined columns in Anatolia are mostly from Synnada which was a property of Roman Empire. The eight-line Hellenic inscription shows that this is dedicated to Zeus Soter. This god was worshipped mostly during the time of war, natural disaster, catastrophe, before and after the long-termed navigations or at a critical time. Based upon its lettering and an epigraphical evidence about Synnadic marble found in Perge, this column is dated to AD II century.